Transition to adult care in cystic fibrosis: The challenges and the structure. (March 2022) - Singh, Jagdev; Towns, Susan; Jayasuriya, Geshani; Hunt, Sharon; Simonds, Sharon; Boyton, Christie; Middleton, Anna; Kench, Andrea; Pandit, Chetan; Keatley, Lucy R.; Chien, Jimmy; Bishop, Jennifer; et al.
Abstract: In developed countries, it is projected that there will be a 70% increase in the number of adults living with Cystic Fibrosis (CF) between 2010 and 2025. This shift in demographics highlights the importance of high-quality transition programmes with developmentally appropriate integrated health care services as the individual moves through adolescence to adulthood. Adolescents living with CF face additional and unique challenges that may have long-term impacts on their health, quality of life and life-expectancy. CF specific issues around socially challenging symptoms, body image, reproductive health and treatment burden differentiate people with CF from their peers and require clinicians to identify and address these issues during the transition process. This review provides an overview of the health, developmental and psychosocial challenges faced by individuals with CF, their guardians and health care teams considering the fundamental components and tools that are required to build a transition programme that can be tailored to suit individual CF clinics.